Pengembangan sumber daya manusia di bidang pariwisata: perspektif potensi wisata daerah kabupaten barru, sulawesi-selatan - Suni, Muhadjir; Badollahi, Muh. Zainuddin (Jurnal Kepariwisataan dan Hospitalitas; Vol 3 No 2 (2019): Vol.3,No.2,2019, 2019)
This paper discusses the strategy carried out by the Barru Regency Government in the Development of Human Resources in the Tourism Sector from the Potential Perspective of his Tour. This research was conducted using a qualitative approach through field studies and literature studies. The results showed that the Barru Regency Government had several strategies intended to maximize the development and management of existing tourism potentials, namely developing natural tourism, embracing the community, and conducting tourism promotions. However, there are still some obstacles faced related to the lack of Human Resources and budget allocations that are not sufficient in processing tourism potential optimally.   Keywords: Development, Tourism Potential, Barru Regency